1975
DOI: 10.2134/agronj1975.00021962006700030003x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Three Warm‐season Perennial Grasses and a Native Range Mixture as Influenced by N and P Fertilization1

Abstract: Several perennial, warm‐season grass species are being used to revegetate depleted rangeland in parts of the southern Great Plains, particularly Oklahoma and Texas. This experiment was conducted to provide comparative data on the yield and quality of forage of three introduced grasses and a native range grass mixture as influenced by nitrogen and phosphorus fertilization. ‘Midland’ bermudagrass [Cynodon dactylon (L.) Pers.], ‘Morpa’ weeping lovegrass [Eragrostis curvula (Schrad.) Nees], ‘Plains’ bluestem [Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 2 publications
4
27
2
Order By: Relevance
“…Our findings agree with an Oklahoma study that observed higher CP and IVDMD concentrations in Midland bermudagrass than in Plains variety of old world bluestem (11). Crude protein levels of Midland 99 were similar in our study to one conducted by Guretzky, but Common, Cheyenne, and Wrangler had considerably higher CP concentrations in our test than were observed in his study (4).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings agree with an Oklahoma study that observed higher CP and IVDMD concentrations in Midland bermudagrass than in Plains variety of old world bluestem (11). Crude protein levels of Midland 99 were similar in our study to one conducted by Guretzky, but Common, Cheyenne, and Wrangler had considerably higher CP concentrations in our test than were observed in his study (4).…”
Section: Discussionsupporting
confidence: 92%
“…Nees], "Plains" bluestem (Bothriochloa ischaemum (L.) Keng var. ischaemum), and native ranges that included switchgrass in Oklahoma [29]. Unlike a previous study where no yield response to 39 kg Pha −1 was observed for switchgrass in Texas [5], the increased yield obtained with 45 kg Pha −1 in this study may have resulted from better stand development, increased soil plant available P, and better P scavenging by the roots.…”
Section: Discussioncontrasting
confidence: 75%
“…Height at cutting had a significant effect on IVDMD content, with an inverse relationship ( Table 2). Taliafero et al (1975) reported that older grasses generally had lower IVDMD contents. There was high correlation between IVDMD and both OMD and NDFD at 48-120 h, Means within the rows with different letters are significantly different at P = 0.05. but correlation was low at shorter incubation times ( Table 5).…”
Section: Resultsmentioning
confidence: 99%